Extending energy access assessment: The added value of taking a gender perspective. (February 2023) - Kooijman, Annemarije; Clancy, Joy; Cloke, Jon
Abstract: Measurement methodologies are increasingly being deployed to monitor energy poverty or energy access, and to provide insights for policy development, both in the South and more recently also in the North. However, care should be taken with interpretation and use of the data, particularly if a gender perspective is lacking. This paper argues that taking a gender perspective is vital to understanding energy access and outcomes related to interventions, through consideration of gendered user differences in energy needs, access to energy services and gendered outcome pathways. We show that the standard practice of focusing on numbers of energy connections, availability and quality of supply, is insufficient to provide insights relevant to realising gender equal access and benefits. It is a political decision about what is measured and who decides on what is measured. Based on the literature, we discuss key elements of the use of gender approaches in the assessment of energy access and energy poverty. We show that by including gender approaches in the design and execution of qualitative and quantitative data collection and analysis, there is the potential to contribute to more equitable outcomes from improved energy access.